The Spiritual Quest in Keisuke Itagaki’s Baki Series A Synthesis of Eastern Religious Figures, Aesthetics, and Martial Arts in a Japanese Anime - Soriano, Rehuel Nikolai (Journal for Religion, Film and Media, 2023)
The Baki series, created by Keisuke Itagaki, is a globally popular anime and manga franchise that has captivated audiences with its striking visual aesthetic and depiction of martial arts. However, despite its widespread popularity, there is a notable lack of scholarly research on the series, particularly in relation to its spiritual and philosophical themes. This research paper aims to address this gap by offering a contextualized analysis of Baki that explores the complex intersection of religion, aesthetics, and pop culture in Japanese society. Through an examination of the series' representation of Eastern religious and philosophical traditions, this study aims to provide insights into the broader cultural attitudes towards masculinity, violence, and martial arts in Japan and the global community. By shedding light on the spiritual themes present in the Baki series, this research seeks to contribute to the global discourse on popular culture, martial arts, and spirituality, offering a nuanced perspective on the multifaceted nature of Japanese culture and its influence on the wider world.